Lactate dehydrogenase-B is silenced by promoter hypermethylation in human prostate cancer. - Leiblich, A; Cross, S; Catto, J; Phillips, J; Leung, H; Hamdy, F; Rehman, I (2006)
In order to identify novel candidates associated with prostate cancer metastasis, we compared the proteomic profile of the poorly metastatic human prostate cancer cell line LNCaP, with its highly metastatic variant LNCaP-LN3, by two-dimensional gel electrophoresis. A major protein spot (pI of 5.9 and molecular weight of 37 kDa) was seen in LNCaP cells, but not in LNCaP-LN3 cells and was identified as lactate dehydrogenase-B (LDHB), by tandem mass spectrometry. Furthermore, enzyme kinetic assays and zymography showed a higher LDH enzyme activity in LNCaP cells compared with LNCaP-LN3. Bisulphite-modified DNA sequencing showed promoter hypermethylation in LNCaP-LN3 cells but not in LNCaP, Du145, PC3, CWR22 or BPH45 cells. Treatment of LNCaP-LN3 cells with 5'-azacytidine caused re-expression of LDHB transcripts. In tissues, LDHB promoter hypermethylation occurred at a higher frequency in prostate cancer, 14/ 31 (45%), compared to adjacent nonmalignant or benign tissue, 2/19 (11%) (P < 0.025). Immunohistochemistry showed a higher frequency of LDHB expression in benign or non-malignant tissues, 59/ 73 (81%), compared to cancer cases, 3/53 (6%) (P < 0.001). Absent LDHB expression was also seen in 7/7 (100%) cases of metastatic cancer in bone. Our data are the first to show loss of LDHB expression in prostate cancer, the mechanism of which appears to involve promoter hypermethylation.